PENGEMBANGAN MEDIA PEMBELAJARAN VLOG (VIDEO BLOGGING) PADA MATERI PENGETAHUAN DASAR GEOGRAFI DI KELAS X IPS SMA NEGERI 1 TAPA - Abas, Komala Dewi; Nurfaika, Nurfaika; Mohamad, Nurdin; Sutiah, Endang (Geosfera: Jurnal Penelitian Geografi, 2023)
A vlog is a video containing opinions, stories or daily activities which are usually written on a blog. Vlogs can be used as learning media because they are easy to create and manage by anyone. This research aims to develop learning media using Vlog (Video Blogging). The method used in the research is development research with the ADDIE model. The results of this research can be concluded that the development of learning media using Vlog (Video Blogging) has passed validity trials by material experts who got a percentage score of 86.66%, the next validator is a product expert validator who got a percentage score of 95.55% and finally by an expert validator learning which obtained a percentage of 88.57%. The results of students' responses to learning media using Vlog (Video Blogging) Basic Geography Knowledge material were carried out twice, namely a limited scale test and a general scale test. The limited test in class X-1 SMAN 1 Tapa got a result of 87.2%, while the general test in class Vlog (Video Blogging) can be used in the learning process in class related to basic Geography Knowledge material. Keywords: Vlog, Video Blogging, Basic Geography Knowledge, ADDIE